'Her pain [was] my suffering – her relief, my hope': Illness, Empathy and the Ethics of Care in Villette. (3rd April 2021) - Choe, Jian
Abstract : This article considers the practice of care and the ethics embedded therein as represented in Villette, focusing on Lucy Snowe's caring relationship with Miss Marchmont. The episode presents a remarkable narrative of suffering, healing and redemption in which the human experience of caring and being cared for is highlighted. Care, intrinsically relational, involves a complex cognitive, affective and moral interplay between two parties. It sustains the carer as well as the one cared for. The heroine's caring practice, rooted in empathy, receptivity and relatedness, ultimately rehabilitates her own traumatised self. In the fullness of the relationship, both change and achieve a new identity. Here, care is envisioned as an existential affair through which we realise our humanity to the full extent. The novel, written amidst the author's own suffering, illuminates the point that the ethics of care could inspire, sustain and redeem us at the time of illness and vulnerability.